ISLAMIC ENTREPRENOLOGY: THEORIZING A PARADIGM - Kaukab, M. Elfan (International Journal of Psychosocial Rehabilitation, 2020)
Research in entrepreneurship are generally unaware of the typical characteristic of Islamic entrepreneurship by assuming that Islam is not different from any other religions that construct demographic variable, and by regarding that Islam is fatalistic and, as a system, it has failed to bring economic prosperity to human kind. This article highlights these mistakes and proposes Islamic entreprenology as a new discipline covering the development of entrepreneurship models which shape the Islamic entrepreneurship concept as a whole and the mechanisms enabling these models to be manifested in entrepreneurial individual behavior. This article provides urgency, limitation, philosophical foundation, aim, approach, and the scope of Islamic entreprenology. It will be the first phase in Islamic entreprenology development to gain stronger recognition among the academics. Recommendation is put forward to initiate the next phase in advancing Islamic entreprenology through conferences, journal development, and next research’s direction.